Chamchaml Citadel based on the historical sources 1820-2013 - Dr. Omed Xatab Wahab; Dr. Jawhar Jalal Wsu (Journal of College of Education, 2025)
Chamchamal citadel is one of the ancient citadels in Kurdistan region- Iraq. Its shape is in circular, the total area of the base of the citadel is larger than its upper part. It was constracted on the steady ground near a water source. The history of the citadel constration is still unknown, so that many different opinions related to its constation histoty have been emerged. There is only a road to clim the citadel, and it is used for many reasons such as: defence, economy, enforcement of the law, …etc. The height of the citadel is different from all its corners, and the castle is located over the main road between Kirkuk and Sulaymaniyah, and control its surrounding. During the Othman Empire rule in the region, a military fort was built there, but it was destroyed in the 1950s. In 1989, Chamchamal Municipality decided to build a defensive wall surrounding the castle as weel as a (1.5) meter fence with eight watchtowers on the castle. The reason behind choosing this topic for the dissertation is that so far there is not a special study about this topic in Kurdistan and Iraq universities. The objective of current study is to answer some questions related to the history of the construction of citadel regarding the explorers and Archaeologists, the hight of the citadel, the objectives behind its constration. Through the current study, method of historical study is depended on in which the knowledge is analyzed, ciompared and then presented. The structure of the study consists of an introdtcion, five main sections, results and list of refrences. Within the introduction, history of chamchaml is refered breavly, the nem of Chamchamal citadel in the historical sources is described while in the second section shape and place of the citadel are explained. Third section is dedivated to explain height, water resources and ways to Ascend the citadel, Fourth section is dedivated to discuss about the history of the citadel construction in the explorers and archaeologists’ points of view, and in the last section, the reasons of building the citadel are described. The study ends with presenting the conclusion of the study .